Terrestrial vegetation and environments on Heard Island - PM Selkirk; DM Bergstrom (Papers and Proceedings of the Royal Society of Tasmania, 2000)
Significantly ice-covered and with a very small flora (11 vascular species and about 60 bryophyte taxa), Heard Island is still emerging from the effects of the last glacial maximum. This study presents the results of a general vegetation survey. A baseline framework of environmental conditions that affect vegetation on the island is described and a classification (TWINSPAN) analysis based on presence/absence data of both vascular plant species and bryophyte taxa is provided. Distinct suites of taxa were identified on the island, some containing bryophytes only. Fifteen ecological groups were delineated. A discussion of ecological amplitude of import ant bryophyte and vascular plant taxa on Heard Island is included.